Laser-induced graphene gas sensors for environmental monitoring - Francis, Cadré; Rektor, Attila; Valayil-Varghese, Tony; McKibben, Nicholas; Estrada, Isaac; Forbey, Jennifer; Estrada, David (Frontiers in Chemistry, 2024)
Low-cost fabrication of sensors is critical for developing large area sensor networks for understanding and monitoring a range of environmental conditions. However, the availability of materials and manufacturing processes are still in the early stages, limiting capacity to develop cost effective sensors at large scale. Here, we demonstrate fabrication of low-cost flexible sensors using laser-induced graphene (LIG); a graphitic material synthesized using a 450 nm wavelength bench top laser patterned on to polyimide substrates. We show the effect of the intensity and focus of the incident beam on the morphology and electrical properties of the synthesized material.Raman analyses of the synthesized LIG show a defect-rich graphene with a crystallite size in the tens of nanometers. This shows that the high level of disorder within the LIG structure, along with the porous nature of the material, provides a good surface for gas adsorption. Initial characterization of the material has shown an analyte response in the presence of volatile organic compounds (VOCs) that are emitted and detected by Artemisia species which is a foundational plant taxa in western North America and an important medicinal plant threated by climate change(1-3). Bend testing provides evidence that these sensors will remain resilient when deployed across the landscapes to assess VOC signaling in plant communities. The versatile low-cost laser writing technique highlights the promise of low cost and scalable fabrication of LIG sensors for gas sensor monitoring.